1991
DOI: 10.1128/jvi.65.9.4812-4820.1991
|View full text |Cite
|
Sign up to set email alerts
|

Fine specificity of cellular immune responses in humans to human cytomegalovirus immediate-early 1 protein

Abstract: Cell-mediated immunity is important in maintaining the virus-host equilibrium in persistent human cytomegalovirus (HCMV) infection. The HCMV 72-kDa major immediate early 1 protein (IE1) is a target for CD8+ cytotoxic T cells in humans, as is the equivalent 89-kDa protein in mouse. Less is known about responses against this protein by CD4+ T cells, which may be important as direct effector cells or helper cells for antibody and CD8+ responses. Proliferative-T-cell responses to HCMV IE1 were studied in normal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Our observations point to a possible regulation of and role for the anti-IEl CD4^ response. They agree with the recent report by He et al [36] who showed that IEl, produced as a fusion protein, induced a protiferative response in 35% of seropositive subjects, and with the results of Alp et al who have also described CD4^ T cells specific for IEl [37]. Our present data confirm, on large populations, these previous reports and extend them by analyses of precursor frequency of anti-IE 1 proliferative cells and demonstration of the variability of anti-IE responses over time.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations point to a possible regulation of and role for the anti-IEl CD4^ response. They agree with the recent report by He et al [36] who showed that IEl, produced as a fusion protein, induced a protiferative response in 35% of seropositive subjects, and with the results of Alp et al who have also described CD4^ T cells specific for IEl [37]. Our present data confirm, on large populations, these previous reports and extend them by analyses of precursor frequency of anti-IE 1 proliferative cells and demonstration of the variability of anti-IE responses over time.…”
Section: Discussionsupporting
confidence: 93%
“…Unfortunately, to date, our knowledge of HCMV CD8 Ï© -Tcell epitopes is limited to only a few, most of which originate from the pp65 lower matrix phosphoprotein (UL83) (25) and some of which originate from the 72-kDa major immediateearly protein (IE-1) (1,9). The presenting HLA molecules, as far as they are known, are HLA-A2, HLA-B7, HLA-B8, HLA-B18, and HLA-B35 (1,9,25), so that only approximately 50 to 60% of a Caucasian population could theoretically benefit from vaccinations or immune therapy based on these known epitopes.…”
mentioning
confidence: 99%
“…Unfortunately, to date, our knowledge of HCMV CD8 Ï© -Tcell epitopes is limited to only a few, most of which originate from the pp65 lower matrix phosphoprotein (UL83) (25) and some of which originate from the 72-kDa major immediateearly protein (IE-1) (1,9). The presenting HLA molecules, as far as they are known, are HLA-A2, HLA-B7, HLA-B8, HLA-B18, and HLA-B35 (1,9,25), so that only approximately 50 to 60% of a Caucasian population could theoretically benefit from vaccinations or immune therapy based on these known epitopes. Despite the existence of several CTL epitopes in IE-1 (1,9) and the observation of IE-1-directed CTL activity in early studies on the anti-HCMV T-cell response (2), the pp65 phosphoprotein is presently believed to largely dominate the anti-HCMV CTL response (13,25).…”
mentioning
confidence: 99%
“…The HCMV pp65 (UL83) matrix phosphoprotein appears to be the major target for these CTLs, as well as a dominant target of proliferative response by CD4 + T‐lymphocytes [119,120]. Low frequency CTL responses to gB (UL55), gH (UL75), pp50 (UL44) and pp28 (UL98) [121] as well as CD4 + proliferative responses to IE‐1, gB (UL55), IE‐2, pp71 (UL82) and the MHC class I homologue (UL18) [122,123] can be detected in PMN cells of normal seropositive subjects. Recently, matrix protein‐specific CTLs have been isolated from HCMV‐seropositive bone marrow donors, propagated in vitro, and adoptively transferred to immunodeficient bone marrow recipients, conferring protection against HCMV viremia and pneumonia [118,124].…”
Section: Immune Evasionmentioning
confidence: 99%